2014
DOI: 10.2147/ceor.s65824
|View full text |Cite
|
Sign up to set email alerts
|

Costs and health care resource utilization among chronic obstructive pulmonary disease patients with newly acquired pneumonia

Abstract: BackgroundPatients with chronic obstructive pulmonary disease (COPD) are at increased risk for lung infections and other pathologies (eg, pneumonia); however, few studies have evaluated the impact of pneumonia on health care resource utilization and costs in this population. The purpose of this study was to estimate health care resource utilization and costs among COPD patients with newly acquired pneumonia compared to those without pneumonia.MethodsA retrospective claims analysis using Truven MarketScan® Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Pneumonia was found to be associated with both direct and indirect costs. Some studies have demonstrated that pneumonia increases total direct costs by 1.9–2.5 times for outpatients and by 3.39–4.72 times for hospitalized patients 15,32. In this study, costs were 1.6 times higher in patients with pneumonia compared to those without pneumonia.…”
Section: Discussionsupporting
confidence: 42%
“…Pneumonia was found to be associated with both direct and indirect costs. Some studies have demonstrated that pneumonia increases total direct costs by 1.9–2.5 times for outpatients and by 3.39–4.72 times for hospitalized patients 15,32. In this study, costs were 1.6 times higher in patients with pneumonia compared to those without pneumonia.…”
Section: Discussionsupporting
confidence: 42%
“…Most studies incorporate outcomes via comorbidity-specific assessment, only three incorporate outcomes based on binary presence or sole number of comorbidities [ 50 , 52 ] or odds ratios (OR) for being in the upper 25, “most costly”, patient percentile [ 53 ]. The sample size differs significantly among studies and reaches from 99 patients with COPD and anemia [ 49 ] to 84,130 patients each for a group of COPD patients with or without pneumonia [ 45 ]. Five studies [ 44 , 46 , 48 50 ] used routine data located entirely or partly in the Medicare and Medicaid environment; the rest utilized routine or survey data from other sources.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [ 44 , 46 , 48 50 ] used routine data located entirely or partly in the Medicare and Medicaid environment; the rest utilized routine or survey data from other sources. To control for differences between groups with and without comorbidity, three studies focused on pneumonia as comorbid disease [ 45 , 47 , 48 ], two studies focused on cardiovascular disease (CVD) [ 43 , 54 ], one on anemia [ 44 ], one on sleep apnea syndrome [ 49 ] and two on multiple comorbidities [ 46 , 51 ]. The rest focused on index-based outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…37 The VACS-VC identifies all individuals at the time of the first ICD-9 diagnosis of HIV within the VA; once engaged in care, published data from 2008 support that 80% of HIV-infected Veterans are prescribed ART, only 14% have CD4+ <200 cells/μL, and 86% of eligible patients receive PCP prophylaxis. 38 Additionally, influenza and pneumococcal vaccination rates increase, likely also reflecting better engagement in and greater utilization of healthcare. 38 In our analyses, baseline CD4+ cell count remained significantly associated with CAP, TB and PCP risk.…”
Section: Discussionmentioning
confidence: 99%
“…38 Additionally, influenza and pneumococcal vaccination rates increase, likely also reflecting better engagement in and greater utilization of healthcare. 38 In our analyses, baseline CD4+ cell count remained significantly associated with CAP, TB and PCP risk. We also compared CD4+ prior to hospitalization and found no significant difference between those with and without COPD, suggesting that the association of COPD with risk for these pulmonary infections is less likely to be explained by differences in CD4+ cell count.…”
Section: Discussionmentioning
confidence: 99%